Computer-assisted cognitive behavior therapy for obsessive-compulsive disorder: a randomized trial on the impact of lay vs. professional coaching - Kobak, Kenneth A; Greist, Revere; Jacobi, David M; Levy-Mack, Hollie; Greist, John H (Annals of general psychiatry, 2015)
Background The purpose of the study was to examine the impact of computerized cognitive behavior therapy (CBT) self-help treatment for obsessive-compulsive disorder (OCD) (BT Steps) both alone and when supported by coaching from either a lay non-therapist coach or an experienced CBT therapist. Methods Eighty-seven subjects with clinically significant OCD were recruited through newspaper ads and randomly assigned to receive 12 weeks of treatment with either BT Steps alone ( n = 28), BT Steps with non-therapist coaching ( n = 28), or BT Steps with CBT therapist coaching ( n = 31). Subjects worked on BT Steps at their own pace. Subjects receiving BT Steps alone received a welcome call from the project manager. Subjects randomized to either of the coaching arms received regularly scheduled weekly phone calls for coaching, encouragement, and support. No formal therapy was provided by the coaches; thus, both lay and CBT coaches completed the same tasks. Results All three treatment arms showed a significant reduction in Yale-Brown Obsessive Compulsive Scale (YBOCS) scores, with mean (SD) changes of 6.5 (5.7), 7.1 (6.1), and 6.5 (6.1) for the no coaching, lay coaching, and therapist coaching arms, respectively (all p ’s < .001). These represent effect sizes of 1.16, 1.41, and 1.12, respectively. No significant differences were found between treatment arms on YBOCS change scores, F (2) = 0.10, p = .904, or number of exposures sessions done ( F (2) = 0.033, p = .967). When asked which method of therapy (computer vs. clinician) they preferred, 48% said computer, 33% said face-to-face therapy, and 19% had no preference. Conclusions Results support the use of online self-help for the treatment of moderate OCD. The addition of coaching by either a lay coach or a CBT therapist coach did not significantly improve outcomes.